Consideration of Complementary Error During Design of the Alternating Current Coaxial Shunts - Bedareva E. V. Elena Vyacheslavovna; Tsimbalist E. I. Edvard Ilyich; Epifanova A. A.; Gavrilenko N. A. Natalia Airatovna (2015, 2015)
Title screen